Preparation of ceramic powders based on titanium nitride on heating commercial titanium powder in air; Refractories and Industrial Ceramics; Vol. 49, N 4 - Strokova Yu. I. (2008, 2008)
Theoretical bases arepresented for preparing ceramic powders based on titanium and aluminum nitrides. The basic advantages are formulated for self-propagating high-temperature synthesis of metal nitride powders in air compared with known preparation methods. The main results are summarized and presented for preparing titanium nitride powder with combustion in air of cylindrical and conical specimens of commercial titanium powder. The effect of specimen shape and weight on combustion rate and the final phase composition of the powders obtained is considered. The possibility is demonstrated of preparing titanium nitride with combustion of coarsely dispersed titanium powder in air